How does a retail organisation such as Asda compete/use innovation to gain competitive advantage? - chouhan, Anand (2012)
Innovation is regarded to be a highly important component in the retail sector due to the significant growth of online home shopping. In recent years as technology has advanced retail organisations have used innovation to create and develop new concepts, ideas and processes. Increasingly online shopping concepts have developed in the retail sector and organisations are continuously exploring ways of maintaining a competitive advantage within online shopping. The purpose of the dissertation is to examine and explore in particular how Asda use innovation to gain a competitive advantage through innovation. The following research questions will be addressed in the study. What is Asda’s approach to innovation? What are the mechanisms deployed to the stores for innovation? Examine the relationship between employees at Asda headquarters and Asda stores. Prior to the study existing literature within the retail industry will illustrate currently how the industry is shaped and how the leading firms are successful. Following on from this the study is guided by the innovation audit framework which enables firms to monitor and evaluate existing innovative practices within Asda. The innovation audit consists of five key points which are strategy, learning, building organisations, process and linkages. Semi structured interviews were formed through the innovation audit to interview the participants. From the researcher’s findings there is discontentment between the employees at Asda headquarters and employees within the Asda stores. Demonstrating that there is a lack of communication prior to the implementation of new products and processes. General themes established from the study suggested that while Asda is a successful firm; it is transparent that Asda’s competitive strategies, processes and networks formed to support innovative practices are inconsistent. Inconsistent communication and knowledge from management to employees is inaccurate or non-existent. Consequently, Asda lack the transparent innovative capabilities to be able to sustain innovative practices. Discussions will be formed to analyse how and why Asda may have developed inconsistent innovative practices, thereafter viable solutions to support Asda in terms of achieving competitive advantage through innovation will be discussed